Cisgenics and intragenics: boon or bane for crop improvement - Vasudevan, S. N.; Pooja, S. K.; Raju, Thota Joseph; Damini, C. S. (Frontiers in Plant Science, 2023)
Recent advances in molecular biology and genetic engineering have made it possible to increase agricultural yields when compared to conventional methods. However, lots of challenges are to be addressed due to changing climatic conditions. Although genetically modified organisms (GMOs) have proven their potential in a few crops, but needs to be explored in majority of the field / vegetable crops to overcome food and nutritional security in view of alarming population explosion. In spite of advantages from GMO crops due to the presence of foreign DNA, queries regarding their safety, environmental dangers and health effects needs to be addressed. One of the major environmental issues concerning transgenic crops is the mixing of genetic components across species that cannot hybridize naturally. Due to these limitations, new revolutionary technologies have been developed, such as intragenesis and cisgenesis for the transformation and development of superior plants. While cisgenesis entails genetic modification employing a complete copy of natural genes with their native regulatory components that only belong to sexually compatible species, intragenesis refers to the transfer of unique combinations of genes and regulatory sequence inside the same species. In cisgenesis, the donor genes are the same genes employed in conventional breeding. The two benefits of cisgenics are avoiding linkage drag and making greater use of existing gene alleles. This method significantly shortens the time it takes to breed plants by combining conventional methods with cutting-edge biotechnological tools. Because of this, plant genomes can be altered without causing drastic changes to the whole plant population and the environmental effects of cisgenic plants cannot be compared to those of transgenics. Transgenesis and cisgenesis share the same transformation methods; hence, cisgenic, intragenic and transgenic plants produced through random insertion do not pose any distinct risks with regard to host genome modifications. In contrast, using new genome techniques lessens the dangers related to potential unintentional changes to the host DNA. The use of cisgenesis and intragenesis as alternatives to transgenesis has been restricted to a small number of species due to incomplete understanding of the required regulatory sequences.